A novel assay of excess plasma kallikrein-kinin system activation in hereditary angioedema - Sexton, Dan; Faucette, Ryan; Rivera-Hernandez, Melody; Kenniston, Jon A.; Papaioannou, Nikolaos; Cosic, Janja; Kopacz, Kris; Salmon, Gary; Beauchemin, Chantal; Juethner, Salomé; Yeung, Dave (Frontiers in Allergy, 2024)
BackgroundCleaved high-molecular-weight kininogen (HKa) is a disease state biomarker of kallikrein-kinin system (KKS) activation in patients with hereditary angioedema due to C1 inhibitor deficiency (HAE-C1INH), the endogenous inhibitor of plasma kallikrein (PKa).ObjectiveDevelop an HKa-specific enzyme-linked immunosorbent assay (ELISA) to monitor KKS activation in the plasma of HAE-C1INH patients.MethodsA novel HKa-specific antibody was discovered by antibody phage display and used as a capture reagent to develop an HKa-specific ELISA.ResultsSpecific HKa detection following KKS activation was observed in plasma from healthy controls but not in prekallikrein-, high-molecular-weight kininogen-, or coagulation factor XII (FXII)-deficient plasma. HKa levels in plasma collected from HAE-C1INH patients in a disease quiescent state were higher than in plasma from healthy controls and increased further in HAE-C1INH plasma collected during an angioedema attack. The specificity of the assay for PKa-mediated HKa generation in minimally diluted plasma activated with exogenous FXIIa was demonstrated using a specific monoclonal antibody inhibitor (lanadelumab, IC50 = 0.044 µM).ConclusionsAn ELISA was developed for the specific and quantitative detection of HKa in human plasma to support HAE-C1INH drug development. Improved quantification of the HKa biomarker may facilitate further pathophysiologic insight into HAE-C1INH and other diseases mediated by a dysregulated KKS and may enable the design of highly potent inhibitors targeting this pathway.